Sufism as the Core of Islam: A Review of Imām Junayd Al-Baghdadī’s Concept of Taṣawwuf - Cucu Setiawan; Maulani Maulani; Busro Busro (Teosofia: Indonesian Journal of Islamic Mysticism, 2020)
This paper studies the thought of the Persian mystic Junayd al-Baghdadī, a prominent figure in the early development of Sufism (taṣawwuf). This study attempts to determine the relationship between Sufism and Islam and test the popular assumption that Sufi ideas and practices corrupt the original Islamic teachings and thus constitute innovation (bidʿa). This quantitative study focuses on the Rasāʿil Junayd (Epistles of Junayd) as the primary source of data and concludes that Sufism is not only based on authentic Islamic teachings but represents the spiritual core of Islam. Junayd al-Baghdadī formulated its three central concepts of the covenant (mīthāq), annihilation (fanāʾ), and unification (tawḥīd). He successfully reconciled the spiritual concepts of taṣawwuf and the legal concepts of fiqh and thus helped to free Sufism from the stigma of heresy and integrated it into mainstream Islam.